A market-based approach to marine sand resource management in the Pearl River estuary, China. (March 2015) - Zhao, Mingli; Yang, Dewei; Wang, Ping; Shi, Ping
Abstract: The Pearl River estuary is a microcosm of marine sand resource management issues, which are being experienced in many developing coastal regions in China. The increasing demand and inefficient management of marine sand have resulted in a series of environmental problems and raised great challenges for rational utilization of marine sand. In the long term, resolving management conflicts and improving the efficiency of resource utilization will require a shift in management approach from administrative examination and approval (AEA) of sector-based management to market-based approach of cooperation management. This paper concerns a pilot scheme for market-based resource allocation, and illustrates how the involved agencies could work together to push forward the scheme in a sectoral context. Both achievements and inadequacies of the scheme are presented, and enabling factors are identified, which include administrative authorization, institutional support and approach improvement, which facilitate the success of the scheme. We also describe key elements (a clearly defined exchange object, independent third-party trade platform and standardized market rules, rational goals, and cooperation mechanism), which are essential for a market-based approach to manage marine sand. We hope the experience acquired in the Pearl River estuary will be useful for other coastal regions in the world. Highlights: Administrative structure and allocation approach are vital for efficient marine sand management. We identify key elements that are essential for market-based approach to manage marine sand. Market-based approach maximizes economic value of sand resources and reduces the influence of informal power. The administrative authorization, institutional support and approach improvement are the enabling factors.